Ancillary findings assessed by ventilation/perfusiont omography - Begic, A.; Opankovic, E.; Cukic, V.; Lindqvist, A.; Miniati, M.; Bajc, M. (Nuklearmedizin - NuclearMedicine, 2015)
Ventilation/perfusion tomography (V/P SPECT) is a recommended method for diagnosing and follow-up of pulmonary embolism (PE). Moreover, it is possible to recognize other pathologies in addition to PE, such as pneumonia, COPD and left heart failure (LHF). The objective of this prospective study was to identify frequency of ancillary findings among patients with suspected PE. Patients, material, method: 331 consecutive patients with suspected PE were examined and classified with V/P SPECT. Patients were followed up clinically and by means of other laboratory tests. Results: 80 patients had a normal V/P SPECT and no clinical consequences in the follow-up. PE had 104 patients: 23 of them had also additional findings. Among the remaining 147 patients, pneumonias were shown in 82, acute in 75 patients and 7 had chronic post inflammatory state. COPD was present in 42 patients, in 3 combined with pneumonia. Sign of LHF was observed in 10: in 7 the acute LHF diagnosis was established, 3 were classified as having a chronic cardiopulmonary disease. Furthermore, in 16 patients, the V/P pattern was suggestive of a tumour. The clinical outcomes were 6 lung tumours, 3 empyema, one sarcoidosis, 2 were unclarified and 4 were lost in the follow-up. Conclusion: V/P SPECT identifies a high prevalence of other cardiopulmonary diseases among patients with a clinical suspicion of PE. Ancillary findings with V/P SPECT clarified patients' symptoms and had an impact on the treatment. These findings were verified by a clinical outcome by the follow-up over three months.
Keywords: V/P SPECT; pulmonary embolism; ancillary finding; clinical outcome